PTH-093 Portal Vein Thrombosis. (17th August 2016) - Malik, A; Yeoman, A; Allison, M; Czajkowski, M
Abstract : Introduction: Portal vein thrombosis (PVT) is defined as the presence of thrombus in the trunk of PV and/or its right and left intra-hepatic branches. PVT can be classified as acute or chronic, intra or extra-hepatic and occlusive or non-occlusive. Patients may be asymptomatic or present with upper GI bleeding or abdominal pain. PVT in cirrhotic patients can present with acute decompensation such as ascites or variceal bleeding. Methods: A retrospective review of all radiological diagnoses of PVT was done with a view to understanding the aetiology, clinical spectrum, treatment and prognosis of patients managed under a large district hospital. Results: A total of 115 patients, median age 62 years (range 25 to 90) were diagnosed with PVT between 2010 and 2015, of whom 71 (62%) were male. Usual indications for radiological investigations were abdominal pain, weight loss and decompensation or routine surveillance in cirrhotic patients. PVT was intra-hepatic alone in 29 patients and extra-hepatic with or without intra-hepatic extension in the rest. Cavernous transformation was reported in 11 patients. PVT was most commonly seen in association with abdominal malignancy (55 cases – 48%) being due to HCC in 21 cases and other local or metastatic abdominal malignancy in 34. PVT was observed to be due to pancreatitis in 21 cases, liver cirrhosis without HCC in 15, acute diverticulitis/cholecystitis in 6, post surgical in 4 with no clear cause identified in just 14 cases (12%). Thrombophilia screening was performed in 11/14 patients with unclear aetiology and was positive in 3 (1 JAK-2 positive, 1 elevated anti-b2GP1 antibodies, 1 low in both protein C and S, rest negative), 2/15 patients with liver cirrhosis (both negative) and 4/86 (1 positive for lupus anti-coagulant) of remaining patients. In total 24 patients were anticoagulated whilst 3 patients were already on warfarin for atrial fibrillation. Of these, 10 were patients of unclear aetiology, 4 with cirrhosis without HCC, 3 had diverticulitis, 3 local or metastatic malignancy, 2 pancreatitis, 1 cholecystitis and 1 post surgical. Eleven of the 15 patients with cirrhosis and PVT died, typically from hepatic decompensation with a median life expectancy of 8 months (range 1–48 months). Patients who were anticoagulated survived for 12 months as opposed to 4 months for those not anticoagulated. Conclusion: PVT has a wide aetiological spectrum and management strategies are highly variable reflecting the diversity of causes. Anticoagulation was most likely to be commenced in those with no clear cause even in the absence of thrombophilia. This study confirms that PVT in the context of cirrhosis is an adverse prognostic indicator even in the absence of HCC. Disclosure of Interest: None Declared